2019
DOI: 10.4111/icu.2019.60.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Quick Sequential (Sepsis related) Organ Failure Assessment: A high performance rapid prognostication tool in patients having acute pyelonephritis with upper urinary tract calculi

Abstract: Purpose To analyze the utility of quick Sequential Organ Failure Assessment (qSOFA) in patients with uro-sepsis due to acute pyelonephritis (APN) with upper urinary tract calculi, we conducted this study. The role of qSOFA as a tool for rapid prognostication in patients with sepsis is emerging. But there has been a great debate on its utility. Literature regarding utility of qSOFA in uro-sepsis is scarce. Materials and Methods Ours was a retrospective study including 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…Finally, in the current study, the rate of in-hospital mortality was 7%, which appears to be relatively high. This is, however, nearly equivalent to the rate in previous studies [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…Finally, in the current study, the rate of in-hospital mortality was 7%, which appears to be relatively high. This is, however, nearly equivalent to the rate in previous studies [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…In the comparison between CRB and CRB-65, despite the addition of age as a parameter, CRB-65 was statistically superior only in predicting in-hospital mortality (p = 0.02). In previous studies that compared the effectiveness of prediction by qSOFA and SIRS in UTI patients, qSOFA had a higher predictive accuracy for in-hospital mortality and ICU admissions than SIRS [25,26]. Likewise, in our study, the ability of qSOFA to identify the requirement of ICU admission and in-hospital mortality in patients with UTI was better than that of SIRS.…”
Section: Discussionsupporting
confidence: 55%
“…These patients presented higher rates of clinically significant complications (Clavien ≥ 2), with a total of 6 (26%) cases. Historically, hospital lengths of stay of patients with OPN vary from 4.25 to 12 days [22,27,1]. This study demonstrated that patients from the Post-Covid group had a significantly higher length of stay when compared to the Pre-Covid group (7.6 vs. 3.8 days; p = 0.007), possibly due to the higher Clavien ≥ 2 complication rates in the first group.…”
Section: Discussionmentioning
confidence: 71%
“…Obstructive pyelonephritis (OPN) is a very common clinical condition in urological practice [1], with high rates of sepsis and Intensive Care Unit (ICU) admissions [2,3], leading to prolonged hospital length of stay and an overall mortality of 2% [4,5]. Obstructive pyelonephritis is an emergency, where targeted treatment [6,7] and prompt decompression of the collecting system [8,9] can potentially improve clinical outcomes, with a high impact on patient morbidity and mortality [10,11].…”
Section: Introductionmentioning
confidence: 99%